2022
DOI: 10.1001/jamaneurol.2022.2456
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neurocritical Care Services With Mortality and Functional Outcomes for Adults With Brain Injury

Abstract: ImportanceNeurocritical care (NCC) aims to improve the outcomes of critically ill patients with brain injury, although the benefits of such subspecialized care are yet to be determined.ObjectiveTo evaluate the association of NCC with patient-centered outcomes in adults with acute brain injury who were admitted to intensive care units (ICUs). The protocol was preregistered on PROSPERO (CRD42020177190).Data SourcesThree electronic databases were searched (Ovid MEDLINE, Embase, Cochrane Central Register of Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…A recent meta-analysis suggested improved survival and better functional outcomes in brain-injured patients treated in specialized neurocritical care units. 26 In our study, most of the patients were treated in general ICUs, and it is not known to what extent outcomes would have differed if all of them had been treated in neuro-ICUs.…”
Section: Discussionmentioning
confidence: 84%
“…A recent meta-analysis suggested improved survival and better functional outcomes in brain-injured patients treated in specialized neurocritical care units. 26 In our study, most of the patients were treated in general ICUs, and it is not known to what extent outcomes would have differed if all of them had been treated in neuro-ICUs.…”
Section: Discussionmentioning
confidence: 84%
“…This is important not only for the surgical aspect but also to facilitate appropriate care in a specialized environment [1,3,[6][7][8]. Moreover, a recent systematic review and meta-analysis showed that neurocritical care services are associated with improved survival and functional outcomes in critically ill adults with brain injury [20].…”
Section: Transfer To the Hub Centermentioning
confidence: 99%
“…venous drainage in the spoke center and during transfer to the hub center Strong recommendation20 We recommend that in severe TBI patients, the head should be maintained in the midline avoiding compression of the neck veins in the spoke center and during transfer to the hub center Strong recommendation21 We recommend avoiding core body temperature > 37.5 °C and to aim for normothermia in severe TBI patients Strong recommendation22 We recommend maintaining Hb level > 7 g/dl in severe TBI patients28 We recommend an increase in sedation, while maintaining an acceptable ABP, as a therapeutic maneuver that should be utilized in the management of patients with signs of brain herniation awaiting emergent neurosurgeryStrong recommendation TBI, traumatic brain injury; ICP, intracranial pressure; ICU, intensive care unit; OR, operating room; CT, computed tomography; GCS, Glasgow coma scale; ABP, arterial blood pressure; ECG, electrocardiogram; HR, heart rate; SpO 2 , peripheral oxygen saturation; ETCO 2 , end-tidal carbon dioxide; MAP, mean arterial pressure; SAP, systolic arterial pressure; PLT, platelet; PT, prothrombin time; aPTT, activated partial thromboplastin time; POC, point-of-care; TEG, thromboelastography; ROTEM, rotational thromboelastometry; EEG, electroencephalogram; Hb, hemoglobin; PaCO 2 , arterial partial pressure of carbon dioxide; Na, sodium Page 5 of 12 Picetti et al World Journal of Emergency Surgery (2023) 18:5…”
mentioning
confidence: 99%
“…Moreover, the need for intensive care for AIS has increased due to the aging population and innovative reperfusion therapy (including intravenous thrombolysis and mechanical thrombectomy). Meanwhile, subspecialized neurocritical care (NCC) delivery was linked with lower mortality and better functional results in patients with acute brain injury [ 4 ]. Hence, identifying the risk factors for poor results early on should be considered to determine the appropriate population for advanced therapy and specific NCC services.…”
Section: Introductionmentioning
confidence: 99%